Assessment of Risk Factors of Cardiovascular Diseases and Arterial Stiffness in Women of Different Ages - O. S. Ivanova; E. Y. Maychuk; I. V. Voevodina (Архивъ внутренней медицины)
Objective: A comprehensive study of the prevalence and structure of risk factors (RF) of cardiovascular diseases (CVD), the daily dynamics of central aortic pressure and arterial stiffness in healthy women of different age groups.Materials and methods: the study involved 161 women aged 18 to 65 years with one or more CVD RF. All volunteers underwent a survey, 24-hour blood pressure monitoring with determination of arterial stiffness and daily dynamics of central aortic pressure, determination of carotid-femoral pulse wave velocity (cfPWV) and vascular stiffness by volume sphygmography.Results: the examined were divided into 3 groups: 1 group of 52 women of young age from 18 to 30 years (23.8 Ѓ} 5.3 years); 2 group of 54 women from 31 years before the onset of menopause (41 Ѓ} 5.9 years); group 3 — 54 women in the postmenopausal period (55.4 Ѓ} 5.8 years). High prevalence of modifiable CVD RF among women of various ages was revealed: smoking, non-compliance with dietary recommendations, lack of physical activity. Obstetric and gynecological pathologies prevail in younger age groups. In group 1 the studied parameters correspond to normal in most parameters. Significant differences in central and peripheral pressure, arterial stiffness indicators, with the exception of cfPWV, were identified in group 2 in comparison with young women. A comparative analysis of groups 2 and 3 showed a significant difference and worsening of indicators characterizing the degree of development of arterial stiffness, the contribution of the reflected wave and the associated dysfunction of the left ventricle.Conclusion: a comprehensive study of arterial stiffness allows you to identify subclinical changes in the vascular wall and evaluate their progression in women of different age groups.